Multiomics reveals multilevel control of renal and systemic metabolism by the renal tubular circadian clock - Yohan Bignon; Leonore Wigger; Camille Ansermet; Benjamin D. Weger; Sylviane Lagarrigue; Gabriel Centeno; Fanny Durussel; Lou Götz; Mark Ibberson; Sylvain Pradervand; Manfredo Quadroni; Meltem Weger; et al. (The Journal of Clinical Investigation, 2023)
Circadian rhythmicity in renal function suggests rhythmic adaptations in renal metabolism. To decipher the role of the circadian clock in renal metabolism, we studied diurnal changes in renal metabolic pathways using integrated transcriptomic, proteomic, and metabolomic analysis performed on control mice and mice with an inducible deletion of the circadian clock regulator Bmal1 in the renal tubule (cKOt). With this unique resource, we demonstrated that approximately 30% of RNAs, approximately 20% of proteins, and approximately 20% of metabolites are rhythmic in the kidneys of control mice. Several key metabolic pathways, including NAD+ biosynthesis, fatty acid transport, carnitine shuttle, and β-oxidation, displayed impairments in kidneys of cKOt mice, resulting in perturbed mitochondrial activity. Carnitine reabsorption from primary urine was one of the most affected processes with an approximately 50% reduction in plasma carnitine levels and a parallel systemic decrease in tissue carnitine content. This suggests that the circadian clock in the renal tubule controls both kidney and systemic physiology.